Histological Study of Pregnant albino Rat Treated with Nickel Oxide Nanoparticles (Medico Legal Update, 2020)
The present study was aimed to elucidate the effect of Nickel oxide nanoparticles (100 mg / kg b.wt ) on some parameters in pregnant Albino rats,in both period of pregnancy (12 and14 days ). 30 albino rats were used; 20 female and the rest 10 were fertilized male rats which were used insemination only, the study including, maternal relative body weight, weight gain measurements and relative organ weights and histological study. Relative body weight of mothers showed decreases in both period of pregnancy. Body weight gain of the pregnant rat show decreases in 14 days of pregnancy in treated group as compared with control group while in 12 days of pregnancy showed increases in treated group as compared with control. Relative organ weight showed increases in (Lung, Uterus, kidney) in treated group and decreases in (Heart, Liver, Eye, Spleen, Brian) in (12) day of pregnancy. In ( 14 ) day of pregnancy showed decreases in (Heart, Liver, Eye, Brian , Kidney) and increases in (Lung, Spleen, Uterus) in treated group as compared with control group Histological study included some organ (liver, spleen, kidney, lung brain, eye and heart) for different period (12, 14) days of pregnancy.